Evaluation of Helianthus annuus L. tolerance for Zinc in vitro post combination with Naphthalene acetic acid and Benzyl adenine - Zainab F. Mahmood; Kadhim M. Ibrahim (World Journal of Experimental Biosciences, 2017)
The tolerance of zinc (Zn) in tissue culture and whole plant Helianthus annuus was studied. Callus was induced and maintained on Murashage and Skoog (1962) medium (MS) supplemented with 0.2 mg/L Kinetin (KIN), 0.4 mg/L Naphthalene acetic acid (NAA) and 0.5 mg/ L 2,4- dichlorophenoxy acetic acid (2,4-D) used hypocotyl as the source explant for callus induction. Different concentrations of Zn were added directly to the culture medium as contaminant. Selected tolerant cell lines were subjected to regeneration. Concentration of Zn in callus tissues was 29 ppm when 3.0 mg/L of Zn used. The study focused on effect of the cytokinin Benzyl adenine (BA) and the auxin, NAA on number of regenerated shoots percentage from tolerant callus to Zn. Results exhibited that 82% of callus-tolerant Zn, occurred when the medium was supplemented with combination of 1.0 mg/L BA and 0.5 mg/L NAA. Effect of NAA on rooting of shoots showed that 2.0 mg/L of NAA gave a rooting percentage mounted to 75%. The study also included measurement of plant height and fresh weight. Maximum Zn accumulation reached to 17.5 ppm in the shoots.
Keywords: Benzyl adenine, callus, Helianthus annuus L., Naphthalene acetic acid, Zinc.